Spatial features, problems and prospects for formation of united territorial communities in Kharkiv region - Кравченко, Катерина (Human Geography Journal, 2017)
In modern conditions of our country great attention of scientists devoted to the problems of improvement of territorial organization regional settlement systems. The process of decentralization of power creates entirely new conditions for the life of the regions of Kharkiv region. Formation of local communities should be focused on providing the public with maximum number of quality services. In every region ofUkrainethere are territories, such as cities, that have a more intense level of development, have better living conditions than the peripheral rural areas. That is why the regional development planning is an important for aligning the economic capacity of the weaker regions on the regional level.The greatest socio-economic level of development will stand out of the community, which include large villages and townships, with important industrial and social facilities for the population with necessary services. With transport links and communication with the regional center of these towns can become new centers of economic development, «growth poles» of the region.Territorial communities legally formed in the Kharkiv region, according to the conditional basis of «preferred habitats residents» divided into: predominantly rural, rural-urban, and predominantly urban. Compared with other regions, the formation of local communities in Kharkiv region is quite slow, which indicates the existence of a significant number of problems. Important issues of formation of local communities in Kharkiv region are: complexity, diversity reform mentality of the population, the uncertainty of development priorities of communities. Among perspectives can be defined: two-level direct funding from the state, local budgets presence in the resource base, and a number of preferences of additional features to attract direct investment.